Carbazole isomers induce ultralong organic phosphorescence - Chen, Chengjian; Chi, Zhenguo; Chong, Kok Chan; Batsanov, Andrei S.; Yang, Zhan; Mao, Zhu; Yang, Zhiyong; Liu, Bin (Nature materials, 2021)
Commercial carbazole has been widely used to synthesize organic functional materials that have led to recent breakthroughs in ultralong organic phosphorescence 1 , thermally activated delayed fluorescence 2 , 3 , organic luminescent radicals 4 and organic semiconductor lasers 5 . However, the impact of low-concentration isomeric impurities present within commercial batches on the properties of the synthesized molecules requires further analysis. Here, we have synthesized highly pure carbazole and observed that its fluorescence is blueshifted by 54 nm with respect to commercial samples and its room-temperature ultralong phosphorescence almost disappears 6 . We discover that such differences are due to the presence of a carbazole isomeric impurity in commercial carbazole sources, with concentrations <0.5 mol%. Ten representative carbazole derivatives synthesized from the highly pure carbazole failed to show the ultralong phosphorescence reported in the literature 1 , 7 – 15 . However, the phosphorescence was recovered by adding 0.1 mol% isomers, which act as charge traps. Investigating the role of the isomers may therefore provide alternative insights into the mechanisms behind ultralong organic phosphorescence 1 , 6 – 18 . A carbazole isomer, typically present as an impurity in commercially produced carbazole batches, is shown to be responsible for the ultralong phosphorescence observed in these compounds and their derivatives.